Testing of the Flame Spread Linear Speed on Foodstuffs and Agriculture Dust Layers - Jan Slosiarik (Communications - Scientific letters of the University of Zilina, 2005)
The paper deals with results of linear speed tests on foodstuffs and agriculture dust layers. The experiments were performed with different samples, focusing on flame spread on the dusts layers occurred in agriculture and food industry.